Lifespan Development A Psychological Perspective - Lally, Martha; Valentine-French, Suzanne; Open Textbook Library (Open Textbook Library, 2017)
This textbook introduces the idea of lifespan development from a psychological perspective.
Chapter 1: Introduction to Lifespan Development -- Chapter 2: Heredity, Prenatal Development, and Birth -- Chapter 3: Infancy and Toddlerhood -- Chapter 4: Early Childhood -- Chapter 5: Middle and Late Childhood -- Chapter 6: Adolescence -- Chapter 7: Emerging and Early Adulthood -- Chapter 8: Middle Adulthood -- Chapter 9: Late Adulthood -- Chapter 10: Death and Dying
In English.
Description based on online resource
Keywords: Social sciences -- Textbooks; Psychology -- Textbooks